Emerging approaches in neurostimulation for epilepsy. Issue 2 (7th April 2023) - Lundstrom, Brian Nils; Osman, Gamaleldin M.; Starnes, Keith; Gregg, Nicholas M.; Simpson, Hugh D.
Abstract : Purpose of review: Neurostimulation is a quickly growing treatment approach for epilepsy patients. We summarize recent approaches to provide a perspective on the future of neurostimulation. Recent findings: Invasive stimulation for treatment of focal epilepsy includes vagus nerve stimulation, responsive neurostimulation of the cortex and deep brain stimulation of the anterior nucleus of the thalamus. A wide range of other targets have been considered, including centromedian, central lateral and pulvinar thalamic nuclei; medial septum, nucleus accumbens, subthalamic nucleus, cerebellum, fornicodorsocommissure and piriform cortex. Stimulation for generalized onset seizures and mixed epilepsies as well as increased efforts focusing on paediatric populations have emerged. Hardware with more permanently implanted lead options and sensing capabilities is emerging. A wider variety of programming approaches than typically used may improve patient outcomes. Finally, noninvasive brain stimulation with its favourable risk profile offers the potential to treat increasingly diverse epilepsy patients. Summary: Neurostimulation for the treatment of epilepsy is surprisingly varied. Flexibility and reversibility of neurostimulation allows for rapid innovation. There remains a continued need for excitability biomarkers to guide treatment and innovation. Neurostimulation, a part of bioelectronic medicine, offers distinctive benefits as well as unique challenges.